Dental caries and Cariostat test in preschool children. - (:unkn) unknown (My University, 1997)
The aim of this study was to investigate the caries status and susceptibility of children in preschool age. Sixty one children ages between 3 to 5 years (mean age 4.38 +/- 0.71) participated in this study. Caries status was assessed according to WHO criteria, and caries susceptibility by using the Cariostat test. The mean df-t was found to be 2.28 +/- 0.71 (df-s 6.26 +/- 11.92) and 31 children were caries-free. Cariostat scores were 1.75, 2.00, 2.16 in the 3, 4, and 5 year age groups respectively. There were no significant differences in caries status or Cariostat scores between boys and girls. The df-t for the 5 year age group was significantly higher than that for the 3 year age groups (p < 0.05). The test found 77% of the children to have a high caries risk (Cariostat score > 2.0).